Analysis of Mixed Methods Graduate Thesis Studies in Special Education Programs in Turkey - Murat DOGAN; Gozde TOMRIS (Anı Publishing, 2022)
This research aims to analyze mixed methods graduate thesis studies completed between 2010 and 2020 in special education programs in Turkey. The literature scan has yielded 26 studies. A qualitative research method, analytical research design has been employed in this study. Research data has been obtained from documents - namely the graduate thesis studies - and analyzed through content analysis carried out following fundamental stages of mixed methods research as proposed in the literature. These stages served as themes in this study: 'Determining the research aim and research questions', 'Selecting a mixed methods research design', 'Explaining the rationale for the mixed methods approach', 'Sampling', 'Collecting the data', 'Analysing the data', 'Integrating, interpreting and reporting the data', 'Researcher competencies and roles' and 'Ethics'. The limitations observed in the methodology and reporting of the thesis studies have suggested that the quality standards of mixed methods research are not reflected on the studies. These limitations include confusion in terminology, lack of explanation as to why the method and the design have been employed, restricted validity and reliability, and lack of integration through blending quantitative and qualitative data. In summary, despite the increase in the number of mixed methods research studies in special education has contributed to the field, it is still debatable whether the philosophical perspective behind the method and its strong suits can be reflected on the studies.